2016
DOI: 10.1051/0004-6361/201526100
|View full text |Cite
|
Sign up to set email alerts
|

Dense gas in the Galactic central molecular zone is warm and heated by turbulence

Abstract: Context. The Galactic center is the closest region where we can study star formation under extreme physical conditions like those in high-redshift galaxies. Aims. We measure the temperature of the dense gas in the central molecular zone (CMZ) and examine what drives it. Methods. We mapped the inner 300 pc of the CMZ in the temperature-sensitive J = 3-2 para-formaldehyde (p-H 2 CO) transitions. We used the 3 2,1 −2 2,0 / 3 0,3 −2 0,2 line ratio to determine the gas temperature in n ∼ 10 4 −10 5 cm −3 gas. We ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
326
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(371 citation statements)
references
References 108 publications
(174 reference statements)
36
326
5
Order By: Relevance
“…Other studies have shown that there is no significant difference in the kinetic temperature (Hüttemeister et al 1993;Ao et al 2013;Ginsburg et al 2016) or line width (Jones et al 2012) between the clouds in our study with relatively weak and bright HCN 1-0. Our RADEX analysis then indicates that for a constant column density, temperature, and linewidth, variations in volume density from n=10 5 − 10 7 should change the line brightness by less than a factor of 2.…”
Section: Variation In Excitation Conditionscontrasting
confidence: 67%
“…Other studies have shown that there is no significant difference in the kinetic temperature (Hüttemeister et al 1993;Ao et al 2013;Ginsburg et al 2016) or line width (Jones et al 2012) between the clouds in our study with relatively weak and bright HCN 1-0. Our RADEX analysis then indicates that for a constant column density, temperature, and linewidth, variations in volume density from n=10 5 − 10 7 should change the line brightness by less than a factor of 2.…”
Section: Variation In Excitation Conditionscontrasting
confidence: 67%
“…Such discrepancy between gas and dust temperatures has been observed in the CMZ at 1 pc spatial scales (e.g., Ao et al 2013;Mills & Morris 2013;Ott et al 2014;Ginsburg et al 2016;Immer et al 2016;Krieger et al 2016). Our observations confirm that in the 20 km s −1 cloud high gas temperatures of 50 K continue down to 0.1-pc scales.…”
Section: Gas Temperatures At 01-pc Scalesmentioning
confidence: 86%
“…First, we search for correlations between temperatures and linewidths, assuming the latter to be an indicator of turbulent strength (cf. Ginsburg et al 2016;Immer et al 2016), and between temperatures and H 2 O maser luminosities, assuming the latter to be correlated with protostellar luminosities (Palla et al 1993). Second, we attempt to look for direct signatures of turbulent or protostellar heating from our temperature maps.…”
Section: Turbulent Heating and Protostellar Heatingmentioning
confidence: 99%
“…Formaldehyde (H 2 CO) is a ubiquitous molecule in the Galactic interstellar medium (ISM) of our and external galaxies (Downes et al 1980;Cohen & Few 1981;Bieging et al 1982;Cohen et al 1983;Baan et al 1986Baan et al , 1990Baan et al , 1993Henkel et al 1991;Zylka et al 1992;Hüttemeister et al 1997;Heikkilä et al 1999;Wang et al 2004Wang et al , 2009Mangum et al 2008;Zhang et al 2012;Mangum et al 2013b;Ao et al 2013;Tang et al 2013;Ginsburg et al 2015Ginsburg et al , 2016Guo et al 2016). H 2 CO is thought to be formed on the surface of dust grains by successive hydrogenation of CO (Watanabe & Kouchi 2002;Woon 2002;Hidaka et al 2004): CO → HCO → H 2 CO. Variations of the fractional abundance of H 2 CO do not exceed one order of magnitude.…”
Section: Introductionmentioning
confidence: 99%